1996
DOI: 10.1016/0014-5793(96)01089-7
|View full text |Cite
|
Sign up to set email alerts
|

A systemic antiviral resistance‐inducing protein isolated from Clerodendrum inerme Gaertn. is a polynucleotide:adenosine glycosidase (ribosome‐inactivating protein)

Abstract: Two systemic antiviral resistance-inducing proteins, CIP-29 and CIP-34, isolated from Clerodendrum inerme Gaertn. leaves, were tested for ribosome-inactivating properties. It was found that CIP-29 has the characteristics of a polynucleotide: adenosine glycosidase (ribosome-inactivating protein), in that it inhibits protein synthesis both in cell-free systems and, at higher concentrations, in cells, and releases adenine from ribosomes, RNA, poly(A) and DNA. As compared with other known RIPs, CIP-29 deadenylates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 22 publications
3
23
0
Order By: Relevance
“…Similar results have been reported earlier with antivi ral proteins like MAP from Mirabilis jalapa [29], CIP 29 from Clerodendrum inerme [11], CCP 27 from Celosia cristata [9], and AAP 27 from Amaranthus tricolor [30].…”
Section: Resultssupporting
confidence: 89%
“…Similar results have been reported earlier with antivi ral proteins like MAP from Mirabilis jalapa [29], CIP 29 from Clerodendrum inerme [11], CCP 27 from Celosia cristata [9], and AAP 27 from Amaranthus tricolor [30].…”
Section: Resultssupporting
confidence: 89%
“…The A chain possesses RNA Nglycosidase activity which depurinates a single adenine residue located near the 3 0 terminal end of the 28S rRNA within the a-sarcin/ricin loop (Olsnes et al, 1975;Endo and Tsurugi 1987;Olmo et al, 2001;Hartley and Lord, 2004). This site-specific depurination event prevents binding of elongation factor-2 to the ribosome, thereby causing translational arrest (Oliviery et al, 1996). Pulmonary ricin intoxication is considered most hazardous, the estimated LD 50 being within the mg/kg range (Audi et al, 2005).…”
Section: Introductionmentioning
confidence: 97%
“…However, experimental evidence from various authors (Li et al 1991; Barbieri et al 1992;Ling et al 1994;Roncuzzi and Gasperi-Campani 1996) indicated dierent additional substrate(s) for the enzymatic activity of RIPs. It was shown that at least some RIPs act on RNA species other than ribosomal, including viral RNAs, and on polyadenylic acid [poly (A)], and that all RIPs tested (more than 40) depurinated DNA (Barbieri et al 1994(Barbieri et al , 1997Olivieri et al 1996;Stirpe et al 1996). Thus, RIPs can be more appropriately called polynucleotide:adenosine glycosidases, and this activity may have a role in the antiviral activity besides the inactivation of the host cell ribosomes.…”
Section: Introductionmentioning
confidence: 99%
“…The antiviral activity of plant extracts has been a clue to the identi®cation of new RIPs, and indeed dianthins (from Dianthus caryophyllus, a member of the Caryophyllaceae) were identi®ed in this way (Stirpe et al 1981), and inhibitors of viral infection from the roots of Mirabilis jalapa (Nyctaginaceae; Kubo et al 1990) and from the leaves of Clerodendrum inerme (Prasad et al 1995) turned out to be RIPs (Habuka et al 1990;Olivieri et al 1996). Infection of tobacco plants by tobacco mosaic virus was prevented by leaf extracts from Basella alba (Basellaceae, belonging to the order Caryophyllales as does the family Caryophyllaceae) and from Bougainvillea spectabilis Willd.…”
Section: Introductionmentioning
confidence: 99%